USING ‘ENGLISH SPEAKING PRACTICE’ APPLICATION TO IMPROVE STUDENTS’ SPEAKING SKILL AT THE ELEVENTH GRADE OF SMAN 18 MAKASSAR - Olivia; Dahlia D.Moelier; Restu Januarty Hamid (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
The background of this study based on the fact that speaking skill is the one of the most difficult skill to learn in English. The objective of the study was to know whether there was a improvement on using ‘English Speaking Practice’ application on students’ speaking skill at the eleventh grade of SMAN 18 Makassar. This study used a pre-experimental research method in one class pre-test and post-test. This study conducted at SMAN 18 Makassar. The population in this study was the eleventh grade in the academic year 2022/2023. The number of samples were 20 students from eleventh grade Social Science 4. The writer used the application of SPPS v.25 in conducted the data analysis. The result of this study was using ‘English Speaking Practice’ application can improve students’ speaking skill. It can be proven by the average score obtained by students in the pre-test and post-test. The mean score increased from 48,60 on the pre-test to 82,00 on the post-test. It showed that the hypothesis H1 was accepted and hypothesis H0 was rejected. Based on the analysis above, it could conclude that using ‘English Speaking Practice’ application could improve students’ speaking skill at SMAN 18 Makassar.